2012
DOI: 10.1002/mma.2521
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy analysis method to obtain numerical solutions of the Painlevé equations

Abstract: Communicated by M. EfendievIn this paper, the homotopy analysis method (HAM) is presented to obtain the numerical solutions for the two kinds of the Painlevé equations with a number of initial conditions. Then, a numerical evaluation and comparison with the results obtained via the HAM are included. It illustrates the validity and the great potential of the HAM in solving Painlevé equations. Although the HAM contains the auxiliary parameter, the convergence region of the series solution can be controlled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…By substituting the collocation points (11) into 12, we get the following system of matrix equations…”
Section: The Methods Of Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…By substituting the collocation points (11) into 12, we get the following system of matrix equations…”
Section: The Methods Of Solutionmentioning
confidence: 99%
“…To obtain a system of matrix equations for the fractional derivative, we insert the collocation points (11) into (14) to get…”
Section: The Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hesameddini and Latifizadeh [29] obtained solutions for the first and second types of the Painlevé equations with 8, 10 and 12 iterations. Wang [30] developed an approximate analytical solution of relativistic Toda lattice system and concluded that using HAM may be very effective for solving differential difference equations (DDEs).…”
Section: Homotopy Analysis Methods (Ham)mentioning
confidence: 99%
“…The Painlevé equations, although discovered from strictly mathematical considerations, can be used to describe several physical phenomena 12 including nonlinear waves, statistical mechanics, general relativity, quantum field theory, and quantum gravity. 13 Many powerful methods for constructing the solutions of Painlevé equations have been developed, including the isomonodormy system, 14 the Padé, 15,16 the functional fitting, 17 the Sinc-Galerkin, 18 the homotopy analysis, 19 and the adomian decomposition methods. 20 Recently, Yuan et al presented a new method, named complex method, to get the meromorphic solutions of the Fisher-type equations.…”
Section: Introductionmentioning
confidence: 99%